Trends in Salmonella serovars and antimicrobial resistance in pigs and poultry in Northern Ireland between 1997 and 2016. (8th February 2020) - Porter, Siobhán; Strain, Sam A. J.; Bagdonaite, Gintare; McDowell, Stanley W; Bronckaers, Tamara; Sherrey, Michael; Devine, Paul; Pascual‐Linaza, Ana V.; Spence, Nessie; Porter, Richard; Guelbenzu‐Gonzalo, Maria; Davies, Robert H.; et al.
Abstract : Background: In the EU, salmonellosis is the second most commonly reported zoonosis. This pattern is reflected in Northern Ireland. Historically, foodborne salmonellosis has largely been attributed to the consumption of poultry products, and as such a number of legislative measures have been introduced by the EC. These policies focus mainly on five target Salmonella serovars. Methods: Here the authors present a descriptive analysis of 20 years of data from the Northern Ireland National Reference Laboratory for Salmonella . Results: The study's results show, for poultry submissions, a large decrease in the detection of four of the five targeted Salmonella serovars over the study period, with the fifth serovar undetected throughout the study. Additionally, there was an increase in the detection of a number of other non‐regulated serovars. In pigs, S Typhimurium, which is among the most common causes of human salmonellosis, was the most commonly isolated serovar. When comparing levels of antimicrobial resistance in S Typhimurium between livestock groups, the authors found a decrease over time in poultry, but an increase in pigs, highlighting the potential significance of pigs in addressing public health concerns. Conclusion: The authors conclude that continued surveillance is important in the assessment of control measures at a national and transnational scale.